FAKTOR YANG MEMPENGARUHI KEJADIAN KEPUTIHAN PADA AKSEPTOR KB SUNTIK 3 BULAN - Widya Nengsih; Mega Mustika (Maternal Child Health Care, 2022)
Leucorrhoea is a genetalia's fluid discharge. It is not blood and not a kind disease. However it is a symptom manifestation of uterine diseases. In Guguk Community Health Center on February to March 2018,it was recorded 240 participants used injecting family planning Methodology: The type of this research was descriptive analytic with cross sectional research design. Women who used 3 months injection were the population this research. Then, by using total sampling technique, 118 people were chosen as the samples of this research. Then, the data was analyzedby univariate and bivariate analysis with test Chi Square statistics. The univariate analysis results obtained that 55.9% of the respondents had vaginal discharge. Then, 75.4% of themhad weight gain. Next, 61.0% of the respondents had good personal hygiene. Moreover, the results of bivariate analysisdescribed that there was a relationship between weight gain (p = 0.001 and OR = 4.911), personal hygiene (p = 0.000 and OR =, 065) with vaginal discharge at 3-month injection family planning acceptors in Guguk Panjang Community Health Center Bukittinggi in 2018. In short, it can be concluded that the most related factors of vaginal discharge at 3-month injection family planning was weight gain Keywords         : Leucorrhoea, Three Months Injection